Synthesis, characterization, computational studies and biological activities of Co(II), Ni(II) and Cu(II) complexes of 2-Amino-1, 3, 4-thiadiazole derivatives. Issue 16 (17th September 2018) - Hassan, Ahmed E.; Shaaban, Ibrahim A.; Abuelela, Ahmed M.; Zoghaib, Wajdi M.; Mohamed, Tarek A.
Abstract: Co(II), Ni(II), and Cu(II) complexes of 2-Amino-5-ethyl-1, 3, 4-thiadiazole (AET) and 2-Amino-5-(ethylthio)-1, 3, 4-thiadiazole (AEST) have been synthesized and characterized based on elemental analysis, magnetic susceptibility, infrared (4000–400 cm −1 ), mass spectrometry (ESI and MALDI), UV–Vis (200–1100 nm) and thermal analysis (TGA/DTA). Molar conductance measurements proved that [ M (L)2 (H2 O)2 ]Cl2 ·H2 O are electrolytic complexes where M represents Co, Ni, and Cu divalent metal ions. The geometrical isomerism of [ M (L)2 (H2 O)2 ] 2+ ions were investigated by DFT-B3LYP calculations incorporated in Gaussian09 package; it favored the all trans isomers due to having the lowest energy points on the potential energy surface. The outcome of DFT-B3LYP quantum mechanical calculations using 6-31G(d) basis set favor six-coordinate sites via a bidentate ligand through exo amino and adjacent endo thiadiazole nitrogen (N3 ) donors. These results were consistent with magnetic measurements combined with infrared and UV–Vis spectral interpretations. The predicted metal–ligand binding energies from B3LYP/6-31G(d) calculations follow the trend Cu 2+ >Ni 2+ >Co 2+, in agreement with the Irving–Williams series. Both AET and AEST ligands and the synthesized complexes were screened for their antibacterial activity and the outcome was high antimicrobial activity of the complexes compared to the free ligands against one or more microbial species and in some cases (copper complexes) higher activity than standard drugs. Graphical Abstract: